The Design of Everyday Things, revised and expanded edition - Norman, Donald A. (MIT Press, 2013)
Even the smartest among us can feel inept as we try to figure out the shower control in a hotel or attempt to navigate an unfamiliar televis ion set or stove. When The Design of Everyday Things was published in 1988, cognitive scientist Don Norman provocatively proposed that the f ault lies not in ourselves, but in design that ignores the needs and p sychology of people. Fully revised to keep the timeless principles of psychology up to date with ever-changing new technologies, The Design of Everyday Things is a powerful appeal for good design, and a reminde r of how – and why – some products satisfy while others only disappoin t.